2019
DOI: 10.1016/j.taap.2019.02.006
|View full text |Cite
|
Sign up to set email alerts
|

PCB 126 induces monocyte/macrophage polarization and inflammation through AhR and NF-κB pathways

Abstract: Polychlorinated biphenyls (PCBs) are persistent organic pollutants that contribute to inflammatory diseases such as atherosclerosis, and macrophages play a key role in the overall inflammatory response. Depending on specific environmental stimuli, macrophages can be polarized either to pro-inflammatory (e.g., M1) or anti-inflammatory (e.g., M2) phenotypes. We hypothesize that dioxin-like PCBs can contribute to macrophage polarization associated with inflammation. To test this hypothesis, human monocytes (THP-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 57 publications
5
41
0
Order By: Relevance
“…The mechanism of TCDD- and PCB-induced atherosclerosis has been well characterized by many studies [ 21 , 23 , 39 , 40 ]. Emerging data continue to demonstrate the participation of miRNAs in atherosclerosis [ 41 43 ] and in biological responses induced by environmental pollutants [ 44 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of TCDD- and PCB-induced atherosclerosis has been well characterized by many studies [ 21 , 23 , 39 , 40 ]. Emerging data continue to demonstrate the participation of miRNAs in atherosclerosis [ 41 43 ] and in biological responses induced by environmental pollutants [ 44 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Developmental PCB exposures have been linked to disruptions in the microbiome and intestinal physiology [222], liver function [223,224], lipid metabolism [225], and systemic inflammation [226,227]. These outcomes overlap with comorbidities common in ASD [1], raising the question of whether developmental PCB exposures contribute to ASD comorbidities.…”
Section: A Role For Pcbs In Asd Comorbidities?mentioning
confidence: 99%
“…M2 macrophage secretes high level of IL-10 and TGF-β. Its role is immune suppression, tissue repair and functional remodeling (36). Much evidence demonstrated that miRNA level varied in different macrophage polarization.…”
Section: Discussionmentioning
confidence: 99%